2012
DOI: 10.5606/kbbihtisas.2012.059
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of clinical and pathological staging in oral cavity cancers

Abstract: Objectives: This study aims to compare the clinical and pathological TN stages of patients with oral cavity cancer and to identify the factors leading to staging discrepancies. Patients and Methods:The medical records of 125 patients (77 males, 48 females; mean age 57 years; range 19 to 82 years) who underwent primary tumor resection and neck dissection simultaneously for oral cavity cancer were retrospectively analyzed. Clinical and pathological TN stages of all patients were compared. Sensitivity, specificit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
1
0
3
Order By: Relevance
“…However, the discrepancy between clinical and pathologic staging represents an obstacle to perform a direct comparison between these 2 series that were treated at the same institution during the same time period. Previous studies showed stage migration from clinical to pathologic staging in a substantial proportion of OSCC patients, likely due to uncertainty in the physical examination judgement, limited accuracy of radiologic evaluation, occasional resection of the tumor in fragments, shrinkage of the tumor after the fixation process, or presence of occult single or multiple lymph nodes [33] , [34] .…”
Section: Discussionmentioning
confidence: 99%
“…However, the discrepancy between clinical and pathologic staging represents an obstacle to perform a direct comparison between these 2 series that were treated at the same institution during the same time period. Previous studies showed stage migration from clinical to pathologic staging in a substantial proportion of OSCC patients, likely due to uncertainty in the physical examination judgement, limited accuracy of radiologic evaluation, occasional resection of the tumor in fragments, shrinkage of the tumor after the fixation process, or presence of occult single or multiple lymph nodes [33] , [34] .…”
Section: Discussionmentioning
confidence: 99%
“…При этом оба метода дополняют друг друга в оценке опухолевого поражения области головы и шеи. У разных исследователей чувствительность и специфичность МРТ и РКТ в выявлении первичного очага и в дифференциальной диагностике с неопухолевым поражением слизистой полости рта колеблется от 75 до 96 % [3,15].…”
Section: сравнение методов диагностикиunclassified
“…МРТ обладает высокой информативностью в диагностике мягкотканных опухо-лей, поражения костных структур с вовлечением костного мозга, распространения опухоли по костному каналу [15], а также при периневральном росте опухоли [17]. Исследование Imaizumi A. et al показало, что чувствительность и специфичность МРТ в оценке распространения опухолевого процесса на надкостницу и костный канал нижней челюсти составили 96-100 % и 54-70 % соответственно, тогда как при РКТ эти же показатели составили 100 % и 88-96 % соответственно.…”
Section: сравнение методов диагностикиunclassified
“…В этих работах представлены возможности лучевой диагностики первичного очага полости рта и его распро-страненности. Чувствительность и специфичность МРТ и КТ в выявлении первичного очага и дифференциальной диагностике его с неопухолевым поражением полости рта колеблется от 75 до 96% [4][5][6][7][8][9][10]. Детально изучены воз-можности методов лучевой диагностики в определении размера опухоли (по сравнению с данными гистологиче-ского исследования) и распространения плоскоклеточ-ного рака на анатомически важные структуры в работах A. Imaizumi и соавт.…”
unclassified